Virtual synchronous motor based-control of Vienna rectifier. (December 2020) - Yan, Xiangwu; Qin, Fuwei; Jia, Jiaoxin; Zhang, Ziyu; Li, Xiaoyu; Sun, Ying
Abstract: Vienna rectifiers are widely used because of their advantages of high power-factor, low voltage stress on the power semiconductor switches, high power density, stable output voltage, low current harmonic content, and good economics. And gradually applied to the front stage AC/DC part of the electric vehicle charger. Traditional Vienna rectifier control methods include double closed-loop control, hysteresis current control, and Sliding mode variable structure control strategy, but all strategies usually regulate DC-Voltage and keep the unity power factor. However, if it is used for the interface part of the electric vehicle charger with frequent load switching, it is necessary not only to ensure the stability of the output voltage and low THD of the current, but also to be able to respond to the fluctuation of the voltage and frequency of the power system and improve the inertia and damping at the interface. Thereby, the stability of the power grid is improved to a certain extent, and fast-charging is ensured while being grid-friendly. Therefore, this paper proposes to apply the virtual synchronous motor control to the Vienna rectifier to improve the adaptability of the grid to the large-scale access of electric vehicles. Build the topology of the Vienna rectifier in simlink and the modulation method using SVPWM to build a complete model on the basis of VSM.